Self-micro emulsifying drug delivery system: An approach to improve the solubility of Itraconazole - Ahmed, Alifa (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.